Antigen specific B cells in myasthenia gravis patients. Issue 2 (2nd April 2020) - Takata, Kazushiro; Kinoshita, Makoto; Mochizuki, Hideki; Okuno, Tatsusada
Abstract: Myasthenia gravis (MG) is a disease caused by pathogenic autoantibodies against the neuromuscular junction and is characterized by muscle weakness. Most MG patients produce antibodies against the acetylcholine receptor (AChR), but a subset of patients have been found to produce autoantibodies against other components of the neuromuscular junction such as muscle specific tyrosine kinase (MuSK) and low-density lipoprotein receptor-related protein 4 (LRP4). The pathogenicity of these autoantibodies has been studied using polyclonal IgG or serum from MG patients; however, pathogenic B cells and monoclonal antibodies from these patients have rarely been investigated because of the difficulty in isolating them. Recently, isolation of pathogenic B cells from MuSK-MG patients and the subsequent generation of monoclonal pathogenic antibodies from these cells, was reported. These data revealed the existence of pathogenic IgG3 and IgG4 antibodies and identified a pathogenic mechanism alternative to the inhibition of MuSK phosphorylation. This review discusses research concerning pathogenic B cells in MG patients and rituximab therapy specifically depleting B cells. Accumulating studies show rituximab therapy is more effective in MuSK-MG patients than in AChR-MG patients. Advances in molecular biology may lead to greater understanding of pathogenic B cells in MG patients and thus potentially lead to the development of novel therapies for MG.